2009
DOI: 10.1007/s11832-008-0154-5
|View full text |Cite
|
Sign up to set email alerts
|

Femoral shaft fractures treated with stainless steel flexible nails in children aged between 5 and 12 years at the HUSVP: A two-year follow-up

Abstract: Purpose The purpose of this study is to show our experience with stainless steel flexible nails in the treatment of femoral shaft fractures in children aged between 5 and 12 years and to observe if the type of material used for nails affects the results. Materials A prospective, descriptive study of a series of cases was performed to evaluate patients treated at the Hospital Universitario San Vicente de Pau´l (HUSVP) who had been followed up for at least 24 months. Results The study group was composed of 48 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…This difference may be due to the reason that their study was not randomized. However, similar results between two implants were seen in the study by Rios et al, 12 consistent with our study.…”
Section: Discussionsupporting
confidence: 94%
“…This difference may be due to the reason that their study was not randomized. However, similar results between two implants were seen in the study by Rios et al, 12 consistent with our study.…”
Section: Discussionsupporting
confidence: 94%
“…In a prospective study, Rios et al published equivalent successful results comparing elastic titanium nails to locally manufactured flexible nails made of steel in the treatment of pediatric femur fractures in a trauma center in Colombia [39]. Alternative less costly implants may be considered for study in LMICs.…”
Section: Discussionmentioning
confidence: 99%
“…24 Few studies indicated that the cheaper stainless steel elastic nails are clinically superior to titanium nails for pediatric femoral fixation primarily because of a much lower rate of malunion 25 and provide good, cheap alternative to these expensive nails. 26 A more careful insertion technique is all that is required in stainless steel nails as compared to the titanium nails due to the inadvertent danger of perforating the second cortex with these much stiffer implants.…”
Section: -13mentioning
confidence: 99%